Investment management - Sabina Dsouza; Basil, Hans V; Anitha, S (Ghaziabad P&P Academy, 2025)
Concept of Investment; Fundamental Analysis; Risk and Return; Technical Analysis; Portfolio Management
Keywords: Management and Public Relations